Herbal formulas for detoxification and dredging collaterals in treating carotid atherosclerosis: a systematic review and meta-analysis - Zhang, Leyi; Huang, Xing; Gao, Yonghong; Li, Xiangyu; Kong, Qiao; Chen, Ying; Chang, Jingling; Zhang, Genming; Ma, Yan (Frontiers in Pharmacology, 2023)
Abstract Objective: To systematically evaluate the efficacy and safety of the Chinese medicine detoxification and dredging collaterals in treating carotid atherosclerosis (CAS). Methods: A systematic and comprehensive search of nine relevant domestic and international databases were conducted from their inception until June 2022. The methodological quality of the included trials was evaluated, and the efficacy and safety were comprehensively analyzed. After applying the inclusion and exclusion criteria to the randomized controlled trials (RCTs), the research quality evaluation and data extraction were conducted, followed by a meta-analysis of the selected articles. The Cochrane's Bias risk assessment was utilized to evaluate the quality of the evidence. Results: Of the 2,660 studies initially retrieved, 14 studies were included, involving a total of 1,518 patients. The results of the meta-analysis indicated that the clinical efficacy of the Detoxification and Collateral Dredging method in the treatment of CAS was superior to that of western medicine treatment alone, and the difference was statistically significant [RR=1.23, 95% CI (1.13, 1.34)] Furthermore, carotid intima-media thickness [Mean Difference (MD) = -0.10, 95% CI (-0.13, -0.08)] and Crouse plaque score [MD = -0.54, 95% CI (-0.75, -0.32)] were significantly lower in the Detoxification and Collateral Dredging group compared to the pure western medicine treatment group. The difference was statistically significant. In addition, serum total cholesterol [MD = -0.70, 95% CI (-0.85, -0.55)] and low-density lipoprotein cholesterol [MD = -0.70, 95% CI (-0.85, -0.55)] were lower in the Detoxification and Collateral Dredging group than in the Western medicine group, with all differences being statistically significant. Serum high-density lipoprotein cholesterol was higher in the Detoxification and Collateral Dredging group compared to the pure western medicine group, and the difference was statistically significant [MD=0.17, 95% CI (0.11, 0.23)]. Conclusion: The use of Chinese medicine Detoxification and Collateral Dredging approach in the treatment of CAS may offer benefits in improving carotid atherosclerotic plaque and reducing blood lipid levels, with a safety profile superior to that of western medicine treatment alone.